Modulation of Mesenchymal Stem Cells Mechanosensing at Fluid Interfaces by Tailored Self‐Assembled Protein Monolayers. Issue 5 (9th January 2019) - Jia, Xiaofang; Minami, Kosuke; Uto, Koichiro; Chang, Alice Chinghsuan; Hill, Jonathan P.; Ueki, Takeshi; Nakanishi, Jun; Ariga, Katsuhiko
Abstract: Mechanical cues of cellular microenvironments can modulate cell functions including cell spreading and differentiation. Most studies of cellular functions are performed using a solid substrate, and it is thought that cells cannot spread on fluid substrates because of rapid relaxation, which cannot resist against actomyosin‐based cell contractility. Here, the spreading and growth of anchorage‐dependent cells such as human mesenchymal stem cells at the liquid interface between a perfluorocarbon fluid and the culture medium are observed. It is demonstrated that a monomolecular protein nanosheet self‐assembled at a fluid interface is sufficiently rigid to support cell spreading without additional treatment. Fine tuning of the packing of these proteins at the liquid interface permits tailoring of the mechanics of the protein layer, ultimately allowing for the regulation of cell spreading. The greater stiffness of the protein nanosheets triggers cell spreading, adhesion growth, and yes‐associated protein nuclear translocation. Cell behavior at the fluid interface is explained within the framework of the molecular clutch model. In addition, the freestanding ultrathin protein nanosheets are extremely flexible, easily deformed, and perceived by cells as being much softer. The findings are expected to provide a new perspective for insights into cell–material interactions. Abstract : Self‐assembled protein monolayers with macroscopic size are sufficiently mechanically strong to support mesenchymal stem cell spreading at a fluid interface. Fine tuning of protein packing permits tailoring of the mechanics of the protein monolayer, ultimately allowing the regulation of cell mechanosensing. An interfacial culturing system is promising for the development of next‐generation stem cell culture materials and implant interfaces.